Ventilator-Associated Pneumonia (VAP) assisted by chitosan (Research, Society and Development, 2022)
Introduction: Ventilator-associated pneumonia (VAP) is one of the main causes of nosocomial infections in ICUs, which leads to an increase in length of stay, medical expenses, increases in morbidity and mortality rates, with an increase in antibiotic-resistant bacteria, corroborates in the application of new biomaterials, therefore, chitosan is studied because it has several functional properties, such as antimicrobial. Methodology: The research carried out is a systematic review by consulting online databases to collect information. The main journal databases used for active article searches were: ANVISA, WHO, PUBMED, Science Direct, SCIELO. Results and discussions: The microbial interaction within the biofilm contributes to the PAVM, in this sense there is an implication in antimicrobial therapy, however the resistance to the drugs used validates the need to find new antimicrobial agents, chitosan and its derivatives have versatility, low cost and broad spectrum of antimicrobial activity against gram-positive and gram-negative bacteria, filamentous fungi and yeasts. Conclusion: it appears that a probable way to combat bacterial infections related to mechanical ventilation is chitosan and its derivatives, they have relevant antimicrobial activities and great potential for their use in combating the tenacity of microorganisms.